A Review: The Effect of Synthetic, Mineral, and Vegetable Coolants on Surface Roughness in Machining Processes - Pratiwi, Ayu; Pranoto, Hadi (Institute for Research on Innovation and Industrial System (IRIS), 2025)
Surface quality of machined parts is an important indicator in determining the final performance of engineering components. One of the main factors influencing this parameter is the type of coolant used during the cutting process. This study is a literature review aimed at systematically comparing the effects of synthetic, mineral, and vegetable-based coolants on surface roughness in various machining processes such as turning, milling, and drilling. The literature review method involved searching reputable scientific articles indexed in Scopus, with a focus on quantitative surface roughness data (Ra). The analysis results showed that plant-based coolants provided the best performance, with a reduction in Ra values of up to 55% compared to conventional mineral coolants. Meanwhile, synthetic coolants demonstrated high cooling capabilities but their lubricating properties remained below those of plant-based coolants. Mineral fluids were found to have the lowest performance in terms of surface quality and environmental impact. This study confirms that the use of plant-based fluids, particularly in Minimum Quantity Lubrication (MQL) systems, is a promising solution for achieving efficient, sustainable, and environmentally friendly machining processes.